An artificial blood vessel implanted three-dimensional microsystem for modeling transvascular migration of tumor cells1. Issue 4 (21st February 2015) - Wang, Xue-Ying; Pei, Ying; Xie, Min; Jin, Zi-He; Xiao, Ya-Shi; Wang, Yang; Zhang, Li-Na; Li, Yan; Huang, Wei-Hua
<x xml:space="preserve">Abstract</x> We developed an artificial blood vessel implanted 3D microfluidic system for reproducing vascular functions and transvascular migration of tumor cells. Based on this model, the adhesion and transvascular migration of tumor cells across the artificial blood vessel have been well reproduced.